(3eUjQ eHOC GdSjGOI aj Xd GdYhdeIs (3OQGSI aj GdbGfhf GdOhdj GdYGe GdeYGUQ (B/s - (3GdSYOGhj, eQGO LGHQ eHGQcs ((3GdbGgQI (B:s (3eDSSI GdWhHLj ddJLGQI hGdWHGYI hGdfTQ,s, 2004)
(3GdbGfhf GdOhdj(B.s
Keywords: (3GdYhdeIs; (3SjGOI GdbGfhfs; (3GdbGfhf GdOhdj GdYGes